(untitled) (American Journal of Management, 2021)
This study explores factors that influence individual decisions to conduct multiple, simultaneous interactions, that is, to multicommunicate. We present data indicating that: (a) the Covid-19 pandemic increased the frequency of multicommunication; (b) university students multicommunicate in order to achieve instrumental, interpersonal, and identity goals; and (c) while some university students recognize that multicommunication increases the risks of communication failures, others do not. We offer some suggestions for educators who wish to include multicommunication concepts in their courses. We also suggest that business practitioners (and their managers) should consider instrumental, interpersonal, and identity objectives when they choose between face-to-face and electronically mediated interaction.